Vailidity of y-intercept in tethered and free swimming as anaerobic capacity index - Gomes de Almeida, A.; Kokubun, E. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The slope of linear relationship between distance and time to fatigue (CV-critical velocity), as predicted by the critical power concept, has been applied to assess aerobic fitness in free swimming. Similarly, in tethered swimming, the critical force (CF), which corresponds to the slope of relation between impulse (force x tlim) and time at fatigue (tlim) showed significant correlation with CV, maximal velocity in 400 meters and lactate threshold (Ikuta et al. 1996). There are evidences that the y-intercept of critical power model would be a valid index of anaerobic capacity. This issue has not been consistently studied in CV or CF researches. The maximal accumulated oxygen deficit (MAOD) is accepted as good measurement of anaerobic capacity. Therefore, the aim of present study was verify if the y-intercept of impulse-tlim relationship (Anaerobic swim capacity-ASC), and distance-time relationship (ASCF), are valid measurements of the anaerobic capacity in swimming. Methods Ten (5 female; 5 male) competitive swimmers, 17 ± 2 years, 63 ± 8 kg, 172 ± 12 cm and VO2peak of 3.6 ± 0.5 L.min-1 performed CF test. Each participant performed 3-4 tethered swimming bouts, in separated days, sustaining load in a weight-pulley system until fatigue. The recorded tlim and force data were fitted to the linear regression model (impulse = ASC + CF. tlim). Expired gas was collected throughout the tests by adapted open circuit portable equipment (TEEM 100, Aeroesport). Exhaustive loads VO2 data were utilized to calculate the MAOD, by modified Hill (1996) procedure as follows: MAOD = k.impulse.tlim - accumulated oxygen consumption Maximal swimming performance on 100 m and 200 m were also accessed to obtain the critical velocity and anaerobic swim capacity for free swimming. Results The mean values and standard deviation of regression coefficient (R2) of impulse-tlim relationship and respective parameters, MAOD, maximal velocity in 100 and 200 m, and ASCF are shown in Table 1. The adjustment of tethered swimming data to the regression was excellent. However, correlations between ASC and others variables were not statistically significant. The correlations between ASCF and other variables were all statistically significant. Discussion/Conclusion These findings did not confirm the hypothesis that the ASC is related to anaerobic capacity in swimming. The correlation between ASC obtained in free and tethered swimming was also low, although both were determined according to the critical power model. This latter result suggests that tethered swimming and free swimming could have mechanical differences that do not allow interpreting them interchangeably. Large inter-individual variability in swimming efficiency may explain the low association between ASC and MAOD. These results suggest that the ASC estimated from tethered swim CF test must be interpreted with caution.